MC1R is a potent regulator of PTEN after UV exposure in melanocytes. - Cao, J; Wan, L; Hacker, E; Dai, X; Lenna, S; Jimenez-Cervantes, C; Wang, Y; Leslie, N; Xu, G; Widlund, H; Ryu, B; Alani, R; et al. (2013)
The individuals carrying melanocortin-1 receptor (MC1R) variants, especially those associated with red hair color, fair skin, and poor tanning ability (RHC trait), are more prone to melanoma; however, the underlying mechanism is poorly defined. Here, we report that UVB exposure triggers phosphatase and tensin homolog (PTEN) interaction with wild-type (WT), but not RHC-associated MC1R variants, which protects PTEN from WWP2-mediated degradation, leading to AKT inactivation. Strikingly, the biological consequences of the failure of MC1R variants to suppress PI3K/AKT signaling are highly context dependent. In primary melanocytes, hyperactivation of PI3K/AKT signaling leads to premature senescence; in the presence of BRAF(V600E), MC1R deficiency-induced elevated PI3K/AKT signaling drives oncogenic transformation. These studies establish the MC1R-PTEN axis as a central regulator for melanocytes' response to UVB exposure and reveal the molecular basis underlying the association between MC1R variants and melanomagenesis.